2022
DOI: 10.3389/fphys.2022.849258
|View full text |Cite
|
Sign up to set email alerts
|

Purinergic and Adenosinergic Signaling in Pancreatobiliary Diseases

Abstract: Adenosine 5'-triphosphate (ATP), other nucleotides, and the nucleoside analogue, adenosine, all have the capacity to modulate cellular signaling pathways. The cellular processes linked to extracellular purinergic signaling are crucial in the initiation, evolution, and resolution of inflammation. Injured or dying cells in the pancreatobiliary tract secrete or release ATP, which results in sustained purinergic signaling mediated through ATP type-2 purinergic receptors (P2R). This process can result in chronic in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 125 publications
0
5
0
Order By: Relevance
“…However, tumor growth curves showed a relapse in tumor progression by day 7 after treatment. KPC cells were recently described to produce ADO and express CD73 ( 20 ); thus, to assess whether RFA may be inducing resistant mechanisms during the acute phase in our preclinical model, we studied a very well-known pathway of TME immunosuppression ( 5 , 20 25 ) by determining by HPLC accumulation of AMP, ADO and INO. Our results revealed that ADO was being generated in RFA treated tumors during the acute phase as early as 4 days after treatment, where it was also found enriched in circulation when compared to Sham treated mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, tumor growth curves showed a relapse in tumor progression by day 7 after treatment. KPC cells were recently described to produce ADO and express CD73 ( 20 ); thus, to assess whether RFA may be inducing resistant mechanisms during the acute phase in our preclinical model, we studied a very well-known pathway of TME immunosuppression ( 5 , 20 25 ) by determining by HPLC accumulation of AMP, ADO and INO. Our results revealed that ADO was being generated in RFA treated tumors during the acute phase as early as 4 days after treatment, where it was also found enriched in circulation when compared to Sham treated mice.…”
Section: Discussionmentioning
confidence: 99%
“…Adenosine (ADO) signaling has emerged as a key extracellular nucleoside signaling pathway involved in tumor immunity as it promotes severe immunosuppression when produced at high levels within the TME. ADO is either released from stressed or injured cells or generated from extracellular adenine nucleotides by the concerted action of the ectoenzymes ectonucleoside triphosphate diphosphohydrolase 1 (CD39) and 5′ ectonucleotidase (CD73) that catabolize ATP to adenosine ( 5 ). Additionally, once generated, extracellular ADO can be converted to inosine (INO) via an enzyme named adenosine deaminase (ADA) ( 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the presence of ectonucleotidase triphosphate diphosphohydrolase-1 (CD39), a cell-surface enzyme with catalytic activity, ATP is rapidly converted to AMP, which is the substrate for catalytic conversion to adenosine by CD73. Preclinical models have shown targeting adenosine signaling has potent antitumor effects (12)(13)(14)(15)(16)(17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, A 3 receptor affinity for adenosine was shown to rank higher than A 2B ; however, discrepancies in the role of A 3 receptors have also been observed in the literature, presenting both anti-inflammatory and pro-inflammatory effects. 44,[48][49][50][51][52][53][54] Therefore, at early stages of inflammation, low local concentrations of adenosine may promote immune recruitment via the A 1 receptor while later high adenosine concentrations can suppress immune activity via the A 2A , A 2B , or A 3 receptors. 44,52,55 Adenosine binding to adenosine receptors modulates both the innate and the adaptive immune response to hypoxia, inflammation, and tissue repair.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, A 3 receptor affinity for adenosine was shown to rank higher than A 2B ; however, discrepancies in the role of A 3 receptors have also been observed in the literature, presenting both anti‐inflammatory and pro‐inflammatory effects. 44 , 48 , 49 , 50 , 51 , 52 , 53 , 54 Therefore, at early stages of inflammation, low local concentrations of adenosine may promote immune recruitment via the A 1 receptor while later high adenosine concentrations can suppress immune activity via the A 2A , A 2B , or A 3 receptors. 44 , 52 , 55 …”
Section: Introductionmentioning
confidence: 99%